2012
DOI: 10.7314/apjcp.2012.13.12.6101
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen Resistance and CYP2D6 Copy Numbers in Breast Cancer Patients

Abstract: Background: Breast cancer accounts about one million from total annual ten million new diagnosed cases of neoplasia worldwide and is the main cause of death due to cancer in women. Tamoxifen is the most popular selective estrogen receptor modulator used in anti estrogen treatments. Tamoxifen must be converted into its metabolite endoxifen for biologic effects; this conversion process is catalysed by highly polymorphic cytochrome P450 2D6 (CYP2D6). This study surveyed copy number variation of the CYP2D6 gene an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…34 Moreover, the inhibitory role of miR-31 on metastasis in breast cancer has been demonstrated in previous studies. 7 According to the results achieved in the presented studies, it seems that miRNAs b27, 31, 125, 141, 145, a2196, 200 family, 205, 206, 210, 429, and 499 along with let-7 are the molecules that have pre-apoptotic function and reduce the expression of oncogenic proteins and increase the expression of anti-apoptotic molecules. Accordingly, it may be concluded that the prevention of cancers such as breast cancer is plausible by increasing their expression.…”
Section: Reduced Micro-rnas In Breast Cancermentioning
confidence: 99%
See 3 more Smart Citations
“…34 Moreover, the inhibitory role of miR-31 on metastasis in breast cancer has been demonstrated in previous studies. 7 According to the results achieved in the presented studies, it seems that miRNAs b27, 31, 125, 141, 145, a2196, 200 family, 205, 206, 210, 429, and 499 along with let-7 are the molecules that have pre-apoptotic function and reduce the expression of oncogenic proteins and increase the expression of anti-apoptotic molecules. Accordingly, it may be concluded that the prevention of cancers such as breast cancer is plausible by increasing their expression.…”
Section: Reduced Micro-rnas In Breast Cancermentioning
confidence: 99%
“…7 Interestingly, these micro-molecules increase sharply in breast cancer and in addition to a vital role in making cells immortal, they are involved in metastasis and exacerbating the disease. 7 These miRNAs can be targeted in molecular therapies in breast cancer.…”
Section: Oncogene Micro-rnas In Breast Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, investigations performed by Wegman P, et al (43) in Sweden and Okishiro M, et al (44) in Japan found no relationship of CYP2D6 or SULT1A1 genotypes with survival time. Similarly, Lum DWK, et al (45) analyzed the CYP2D6 genotype and tamoxifen response by meta-analysis, and found no association, while Motamedi S, et al (46) performed a study in Iran, and reported that there was no significant relationship between CYP2D6 copy number and tamoxifen resistance in their patients.…”
Section: Digital Pcr For Sult1a1mentioning
confidence: 99%